2019
DOI: 10.1016/j.tranon.2018.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Vimentin and Non-Muscle Myosin IIA are Members of the Neural Precursor Cell Expressed Developmentally Down-Regulated 9 (NEDD9) Interactome in Head and Neck Squamous Cell Carcinoma Cells

Abstract: Here we demonstrate an interaction between neural precursor cell expressed, developmentally-downregulated 9 (NEDD9) and the cytoskeletal proteins vimentin and non-muscle myosin IIA (NMIIA), based on co-immunoprecipitation and mass spectrometric sequence identification. Vimentin was constitutively phosphorylated at Ser56 but vimentin associated with NEDD9-was not phosphorylated at Ser56. In contrast, NMIIA bound to NEDD9 was phosphorylated on S1943 consistent with its function in invasion and secretion. Treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 66 publications
(136 reference statements)
3
6
0
Order By: Relevance
“…The correlation of E-cadherin expression at the IF with clinicopathological parameters, risk score and lymph node metastasis showed no statistical significance similar to other studies 4 5 12 20 , including parameters such as age, gender, size or stage of the tumour 4 5 12 , worsening pattern of tumour differentiation 3 12 . Based on similar results, it shows that expression of immunomarkers such as E-cadherin may not have an impact on the biological behaviour of these tumours 20 .…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…The correlation of E-cadherin expression at the IF with clinicopathological parameters, risk score and lymph node metastasis showed no statistical significance similar to other studies 4 5 12 20 , including parameters such as age, gender, size or stage of the tumour 4 5 12 , worsening pattern of tumour differentiation 3 12 . Based on similar results, it shows that expression of immunomarkers such as E-cadherin may not have an impact on the biological behaviour of these tumours 20 .…”
Section: Resultssupporting
confidence: 60%
“…The expression of vimentin at IF showed no correlation in the present study, as was seen in a few other studies that showed similar lack of significant correlation with lymph node metastases 5 12 , age, gender, histological differentiation, POI, size and stage of tumour 5 8 . Contrasting with a positive correlation of Vimentin positivity at IF with lymph node metastasis 8 21 degree of differentiation, clinical stage and POI 19 .…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…The most favorable genotype for this locus was GG, which displayed the lowest weight losses during processing. This mutation is an intron variant of the gene NEDD9 , which codes for a focal adhesion protein that acts as a scaffold to regulate signaling complexes important in cell attachment, migration, and invasion [ 47 ], as well as apoptosis and the cell cycle [ 48 ]. Some studies of different authors reported that NEDD9 is essential for the Transforming Growth Factor β (TGF-β) signaling pathway [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lucas et al demonstrated that VEGF-stimulated HNSCC cell migration and invasion was NEDD9-dependent, while immunohistochemical analysis revealed that NEDD9 co-localized to invadopodia with MT1-MMP [307]. Their following studies investigated the role of NEDD9 in secretion of MMPs, MMP-9 and MMP-2 in particular, the formation of invadopodia, as well as the interactions of NEDD9 with vimentin and non-muscle myosin IIA [308, 309]. Consistent with their findings, the high-throughput gene expression profiling of HNSCC tumor samples has shown that overexpression of NEDD9 is associated with invasive HNSCC [310].…”
Section: Introductionmentioning
confidence: 99%